An algorithm for data reconstruction from published articles – Application on insect life tables. Issue 1 (1st January 2019) - Kareithi, D.N.; Salifu, D.; Owuor, N.; Subramanian, S.; Tonnang, E.Z.H.
Abstract: Data collection in life table experiments is generally time-consuming and costly such that data reconstruction of published information provides an avenue to access the original data for purposes of further investigation. In this paper, we present an algorithm that reconstructs life table raw data using a summary of results from published articles. We present the steps of the development and implementation (in the R computer language) of the algorithm, its scope of application, assumptions, and limitations. Statistical background of the algorithm is also presented. The developed algorithm was then applied to reconstruction of life table data of two insect species, Chilo partellus and Busseola fusca, from published information. Welch's two-sample t -test was applied to test the difference between the original and reconstructed data of the insect life stages. C. Partellus results were not significantly different, but, for B. fusca, pupa development time, and larva and pupa development rate were significantly different at the 95% confidence level. It is concluded that the algorithm could be used to reconstruct original data sets from cohort life table data sets of insects, given published information and sample sizes.